Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.biomac.3c00132
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Biofabrication. Coupling Electrochemical and Biomolecular Methods to Create Functional Bio-Based Hydrogels

Abstract: Twenty years ago, this journal published a review entitled "Biofabrication with Chitosan" based on the observations that (i) chitosan could be electrodeposited using low voltage electrical inputs (typically less than 5 V) and (ii) the enzyme tyrosinase could be used to graft proteins (via accessible tyrosine residues) to chitosan. Here, we provide a progress report on the coupling of electronic inputs with advanced biological methods for the fabrication of biopolymer-based hydrogel films. In many cases, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 197 publications
0
0
0
Order By: Relevance
“…Biofabrication 14 has allowed biological components to be assembled on micro-, or nano-scaled electronic devices for biosensing [15][16][17] or even control of biological functions 18 . Here, we enlisted electro-biofabrication 19 of biocompatible hydrogels to facilitate the assembly of enzymes and cells onto electrodes to localize signal transfer. For enzyme assembly, we show the spatially-configurable electrodeposition of a covalently-conjugated gelatin/horseradish peroxidase (HRP) 20 hydrogel film (Figure 2a, Supplementary Fig.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofabrication 14 has allowed biological components to be assembled on micro-, or nano-scaled electronic devices for biosensing [15][16][17] or even control of biological functions 18 . Here, we enlisted electro-biofabrication 19 of biocompatible hydrogels to facilitate the assembly of enzymes and cells onto electrodes to localize signal transfer. For enzyme assembly, we show the spatially-configurable electrodeposition of a covalently-conjugated gelatin/horseradish peroxidase (HRP) 20 hydrogel film (Figure 2a, Supplementary Fig.…”
Section: Mainmentioning
confidence: 99%
“…There was also no need to supplement with message-conveying redox mediators, since the signal was directly transferred from the electrode. Thus, we anticipate virtually any cell or consortia of cells can be assembled and electronically stimulated using this redox-based or other stimulusresponsive, electroassembly methodologies 19,24 .…”
Section: Oxyrs-based Electrogenetic Crispr Activation (Crispra)mentioning
confidence: 99%
“…Chitin, whether in its pure form or in solution, has seen limited utilization, highlighting an immediate necessity for application on a larger scale. While chitosan and related polysaccharides have been extensively used for biocomposite materials/hybrid materials, including soft hydrogels, foams, and solid composite materials. , Lightweight insulation materials based on cellulose-chitosan for practical applications are also already known, stressing the importance of mechanical resistance and low density . Significantly less work has been reported about chitin. In particular chitin-based foams were little explored. For example, graphene oxide/chitin nanofibrils composite foams to dispose pollutants in aqueous solutions or chitin/chitosan-based nanofibril-reinforced starch foams possessed enhanced flammability and mechanical properties through chitin nanofibrils. , As Achinivu et al showed through the extraction of several different chitin biomass sources that processability, appearance, and mechanical properties highly depend on the chitin biomass source .…”
Section: Introductionmentioning
confidence: 99%